REPRESENTATIONAL HANDLING OF POZNAŃ-CRACOW VOICING IN GOVERNMENT PHONOLOGY - Michalski, Grzegorz (Versita Ltd., de Gruyter, 2008)
This article discusses the problem of accounting for Poznań-Cracow voicing in Government Phonology. It is concluded that in order for the process to be handled representationally, Polish words beginning with non-obstruents would need to carry the element {L} as part of the melody at the leftmost skeletal slot. It is explained that although such a move would make a representa- tional analysis of Poznań-Cracow Voicing straightforward, the presence of the element {L} on non-obstruents is against the tenets of the phonological model. The article is organised as follows. Section 1 presents a selection of voice phenomena in Pol- ish. Section 2 introduces the basic concepts of Government Phonology relevant to the analysis. Section 3 summarises Gussmann’s (2007) analysis of voice phenomena in Polish. Section 4 dis- cusses the differences between Warsaw Polish and Poznań-Cracow Polish in terms of voice as- similation. Section 5 briefly summarises two earlier analyses of voice phenomena in Polish that account for Poznań-Cracow Voicing, namely Gussmann’s (1992) SPE-type analysis of SEGMENT- TO-CONSONANT SPREADING, and Rubach’s (1996) Lexical Phonology (LP) analysis of CRACOW SPREAD. Section 6 presents theoretical considerations of why these two analyses cannot be me- chanically translated into GP theoretical machinery. The section also points to the limitations of VOICE ADJUSTMENT with respect to Poznań-Cracow Voicing. Section 7 introduces the flawed idea of enriching the left edge of words with the element {L}, and provides an attempt at a repre- sentational analysis of Poznań-Cracow Voicing using the enriched representation. Section 8 dis- cusses the limitations of the analysis, and proposes an alternative approach to the issue. Section 9 summarises the most important conclusions.
Keywords: Polish; Poznań-Cracow voicing; regressive obstruent voice assimilation; Government Phonology